INFLUENCE OF POPULAR CULTURE ON THE WORLDVIEW OF YOUNG PEOPLE - Urdabayeva Gulnora Mambetaliyevna (Journals Park Publishing, 2024)
This scientific article provides a comprehensive review of the influence of mass culture on the worldview of young people. Mass culture, encompassing various forms of media, entertainment, and popular trends, plays a significant role in shaping the beliefs, values, attitudes, and perspectives of young individuals. Recognizing the importance of understanding this influence, this article examines the theoretical foundations of mass culture, explores its prevalence in the lives of young people, and investigates its impact on their worldview. The article discusses the positive and negative aspects of mass culture, analyzes its influence on identity formation, social relationships, and societal perceptions, and provides recommendations for promoting critical engagement and media literacy among young individuals.
Keywords: Mass culture, Worldview, Young people, Media influence, Beliefs, Values, Attitudes, Perspectives, Media literacy, Identity formation